Empowerment of women farming group of Ketapang village through black turmeric agropreneur - Rindu Handayani; Feni Kurnia; Sujadi Priyansah (Community Empowerment, 2022)
The PKK Team of Ketapang Village was given training on producing black turmeric agropreneurs in an effort to improve the standard of living of the inhabitants of Pangkalarang Hamlet. Agropreneurship is described as a commercial activity whose primary product is agro-based, whether it is conducted off-farm (for example, marketing) or on-farm (for example, farming) (eg cultivation business). This development activity aims to provide an alternative for women, particularly housewives, to be able to make use of their spare time by cultivating black turmeric and becoming an agropreneur who can market the turmeric cultivation's results, thereby improving their living standards and reducing their reliance on the sea's results. Socialization, acquisition of seeds, fabrication of organic fertilizer, transfer of shoots to pots, and supply of e-commerce services are some of the methods used. The result of this activity is that the PKK Pangkalarang is able to produce black turmeric independently and sell it both offline and online.